Satire in the linguistic features of Ahmed Matar's and rhetorical elements of Abolghasem Halat's poetry - Mohammad Amin Ehsani Estahbanati; Enayatollah Sharifpour; Mohammad Reza Sarfi (مطالعات زبانی و بلاغی)
Signs operate within a framework of sign systems; In other words, they become meaningful by being next to each other. Considering the possibility of examining the language systems in humor, it is possible to analyze the discourse of the work by grasping the semiotic meaning of satiric symbols in a work. In humorous/satiric texts, not only is the study of the semantic level and the codes effective in understanding the meaning, but also the attention to the main sources, i.e. the sociology behind the humorous language of the work as a preface, is essential in recognizing the rhetorical and linguistic layers and their implications. Socio-political satire is one of the most important tools for retelling the facts of a society in symbolic and coded language. Ahmed Matar and  Abolghaesem Halat are two renowned poets among contemporary Arabic and Persian satirists who deal with the problems of the society of their time in a symbolic language. Considering the multiplicity of coded levels in the words of Matar and different rhetorical layers of Halat, the present study has focused on the examination of language and rhetoric in the satirical poems of these two poets from a descriptive-analytical approach. Therefore, we have first analyzed Matar's poems based on the linguistic pattern of Roland Barthes's five codes and have then focused on rhetorical analysis of Halat's poems. The scope of this research is the divan of "Al-A'mal al-Shari'ah al-Kamala" by Matar and the divan of "Khoros Lari" by Halat. The results of this study show that Matar uses different types of hermeneutic, semantic, performative, symbolic and cultural codes, and Halat employs different rhetorical, phonetic, lexical, syntactic and ideological layers in the structure of his poems.